EKSISTENSI TRADISI NGAJI PASARAN BULAN RAMADHAN SEBAGAI WARISAN PENDIDIKAN ISLAM NUSANTARA DI YPI AL-ITTIHAD KEDUNGBANTENG TEGAL - Oktaviani (PRODI PAI FIK UNIRA MALANG, 2026)
Abstract This study aims to analyze the existence of the Ramadan ngaji pasaran tradition as a legacy of Nusantara Islamic education at YPI Al-Ittihad Kedungbanteng Tegal. This study employs a qualitative approach using descriptive methods through observation, interviews, and documentation, analyzed inductively. The results of the study indicate that “ngaji pasaran” is a non-formal Islamic educational practice that has been consistently carried out since 2018 and serves not only as a means of studying classical Islamic texts through the bandongan method but also as a medium for transmitting the values of Nusantara Islamic education. This tradition strengthens the continuity of the pesantren’s scholarly network through direct relationships between ustadz and students, emphasizing aspects of scholarly lineage (sanad), etiquette (adab), and blessings (barakah) in the learning process. The educational values fostered include spiritual and religious values, discipline and responsibility, respect for teachers, and social solidarity among students. Amid the development of the digital era, ngaji pasaran remains relevant as a space for religious learning that possesses clear scholarly authority and is capable of strengthening the religious character of participants. Despite facing challenges such as technological distractions, time constraints, and fluctuations in student participation, this tradition endures through institutional support and the commitment of participants to preserving the continuity of the Islamic Nusantara educational heritage. Keywords: Market-based Quran study, a legacy of Islamic education in the Indonesian archipelago, classical Islamic texts.